Initial Results From The Deep HST-ACS Survey Of The Spiral Galaxy M81 - Zezas, Andreas; Gazeas, K.; Gallagher, J.; Mutchler, M.; Levay, Z.; Huchra, J. (American Astronomical Society Meeting Abstracts #210, 2007)
We present the initial results from a deep HST survey of the nearby spiral galaxy M81 with the HST Advanced Camera for Surveys. The survey consists of B and V band observations of 29 ACS fields, totaling to 38 orbits. These observations, together with archival I-band ACS data, provide complete, deep coverage of the D25 area of the galaxy, down to 26-27 mag. This detection limit probes the bulk of early-type (O,B) stars and the population of star-clusters. The main goal of this survey is to characterize the X-ray source population of M81 in the context of its stellar populations and star-formation history. We discuss the analysis of the ACS data (mosaicing, astrometric registration, photometric analysis) and we present high quality images of the galaxy. We also discuss the initial results from the identification of optical counterparts to the X-ray sources detected in deep Chandra observations of M81, and the preliminary study of the stellar populations in individual fields of the galaxy. This work is supported by HST grant HST-GO-10584.01-A and NASA LTSA grant NAG-5-13056.